Konservasi Lingkungan dan Pemanfaatan Mata Air Pura Tirta Empul : Kajian Prasasti Manukaya - Alfan Azzury Sutejo; Ni Ketut Puji Astiti Laksmi; Zuraidah; Hedwi Prihatmoko; Si Gede Bandem Kamandalu (Penerbit BRIN (BRIN Publishing), 2025)
Abstract. Environmental Conservation and the Utilization of the Tirta Empul Temple Spring: A Study of the Manukaya Inscription. Water is a vital element for all creatures on earth. Moreover, for humans, water has a function to fulfill needs both spiritually and profanely (daily needs). One of the springs used to fulfill these two needs is at Tirta Empul Temple. To fulfill spiritual needs, the spring is used as tirtha (holy water) and to carry out the melukat procession. Profane use of this spring is used for several things, such as supplying household water in Manukaya and Tampaksiring Villages, water raw materials for PDAM Gianyar, meeting the water needs of the Tampaksiring Presidential Palace, and finally, irrigating the subaks located downstream of Tirta Empul Temple. Based on this, the things studied in this paper are related to environmental conservation activities and the use of this spring as stated in the Manukaya inscription. Apart from that, it is also necessary to observe the sustainability of conservation activities carried out by local indigenous communities. The research process is divided into three stages, namely data collection (literature study, observation, and interviews), data analysis (descriptive-qualitative and cultural ecology), and finally data interpretation to draw conclusions. The results of this research show that there are environmental conservation efforts and the use of the Tirta Empul spring in the Manukaya inscription. Conservation efforts are also carried out today by indigenous peoples by maintaining the sacredness of the main pond and having awig-awig regarding the prohibition of cutting down trees around Tirta Empul Temple. Keywords: Pura Tirta Empul, Conservation, Prasasti Manukaya, Water Spring Abstrak. Air merupakan unsur yang sangat vital bagi seluruh makhluk di bumi. Selain itu, bagi manusia, air memiliki fungsi untuk memenuhi kebutuhan baik secara spiritual maupun profane (kebutuhan sehari-hari). Salah satu sumber air yang dimanfaatkan untuk memenuhi kedua kebutuhan tersebut adalah di Pura Tirta Empul. Untuk memenuhi kebutuhan spiritual, sumber air tersebut dimanfaatkan sebagai tirtha (air suci) dan untuk melaksanakan prosesi melukat. Pemanfaatan profane sumber air ini dimanfaatkan untuk beberapa hal, seperti penyediaan air rumah tangga di Desa Manukaya dan Desa Tampaksiring, bahan baku air untuk PDAM Gianyar, pemenuhan kebutuhan air Istana Kepresidenan Tampaksiring, dan terakhir, pengairan subak yang terletak di hilir Pura Tirta Empul. Berdasarkan hal tersebut, maka hal-hal yang dikaji dalam tulisan ini terkait dengan kegiatan pelestarian lingkungan dan pemanfaatan sumber air ini sebagaimana tercantum dalam prasasti Manukaya. Selain itu, perlu juga dicermati keberlanjutan kegiatan pelestarian yang dilakukan oleh masyarakat adat setempat. Proses penelitian dibagi menjadi tiga tahap, yaitu pengumpulan data (studi pustaka, observasi, dan wawancara), analisis data (deskriptif-kualitatif dan ekologi kultural), dan terakhir interpretasi data untuk menarik simpulan. Hasil penelitian ini menunjukkan adanya upaya pelestarian lingkungan dan pemanfaatan mata air Tirta Empul pada prasasti Manukaya. Upaya pelestarian juga dilakukan saat ini oleh masyarakat adat dengan menjaga kesakralan kolam utama dan memiliki awig-awig tentang larangan menebang pohon di sekitar Pura Tirta Empul. Kata kunci: Pura Tirta Empul, Konservasi, Prasasti Manukaya, Mata Air